Influence of Motivation, Parents’ Support, Emotional Intelligence and Carieer Planning Toward An Interest to Join Ppg-Sm3t on The Students of Economic Education of Unnes - Puspitasari, Arum; Rusdarti, Rusdarti; Sudarma, Ketut (Universitas Negeri Semarang, 2017)
One of the government's efforts to overcome the problem of education is by organizing PPG-SM3T program. This study aims to determine whether motivation factors, parents’ support, emotional intelligence and career planning affect the interest to follow PPG-SM3T on UNNES Economic Education students either jointly or partially. The population of this study are all students of Economic Education UNNES year 2013 which amounted to 440 students, with a total sample of 82 students. The sampling technique used is Cluster Proportional Random Sampling. Before the instrument was used for data retrieval, an instrument test was performed on 30 students. Data collection method used is questionnaire. Data analysis methods used are descriptive analysis techniques and multiple linear analysis. The results showed that there is influence of motivation, parent support, emotional intelligence and career planning interested to follow PPG-SM3T of 97.60%. While the motivation to be a teacher influence on the interest to follow the PPG-SM3T of 49.42%. Parents’ support affects interest in following the PPG-SM3T by 41.09%. Emotional Intelligence affects interest to follow PPG-SM3T as much as 5.80% and career planning has an effect on interest in following PPG-SM3T of 8.94%.